Analysis of the Composition and Structure of Mangrove Vegetation in the Coastal Area of Lhokseumawe City - Maulana, Arief; Munandar, Munandar; Fithria, Dewi; Edwarsyah, Edwarsyah; Wintah, Wintah (Universitas Teuku Umar, 2024)
The mangrove ecosystem functions as a transitional area between land and sea, has a crucial contribution to coastal areas both ecologically, economically, and socially. This ecosystem is spread across all sub-districts in the coastal area of Lhokseumawe City. This study aims to examine mangrove vegetation and the abundance of gastropods in the area. This study uses a quantitative descriptive method with transect technique and will be carried out from June 1 to August 1, 2024. This research was conducted in Banda Sakti District, Muara Satu District, and Muara Dua District in Lhokseumawe City. The results of the study showed that mangrove vegetation in the area was dominated by main species such as Rhizophora stylosa, Rhizophora mucronata, Avicennia alba, and Avicennia marina. and the gastropods found included T. telescopium, T. palustris, Cassidula nucleus, Littoraria scabra. As for the conclusion, the types of the mangrove found consist of four types, namely A. marina, A alba, R. mucronata and R stylosa. the density of the tree level type R stylosa at station II is 3200 ind/Ha. The value is higher than the type found at station III A. marina of 300 ind/Ha and I. The relative density for the three stations is the same 100 ind/Ha. The INP of the sapling has the same value of 200 ind/Ha and the INP of the seedling level of the mangrove type A. marina R. mucronata, R. stylosa and A. alba. The amount is the same, namely 200 ind/Ha. Then for suggestions, the Government and related agencies in the Lhokseumawe must focus on mangrove management starting from designing procedures for mangrove management so that it is sustainable in the coastal area of Lhokseumawe city for future generations